Ferroelectric Ceramics: Local Distortions in Nanostructured Ferroelectric Ceramics through Strain Tuning (Adv. Electron. Mater. 10/2015). (14th October 2015) - Philippot, Gilles; Albino, Marjorie; Epherre, Romain; Chevallier, Geoffroy; Beynet, Yannick; Manière, Charles; Weibel, Alicia; Peigney, Alain; Deluca, Marco; Elissalde, Catherine; Maglione, Mario; Aymonier, Cyril; et al.
<x xml:space="preserve">Abstract</x> In article number 1500190 Catherine Elissalde and co‐workers successfully obtain nanostructured ferroelectric ceramics (grain size < 20 nm) using the unique combination of fast and low temperature processes including supercritical fluid synthesis and spark plasma sintering in air under high pressure. The stress generated at the nanograin scale can be controlled and used to tune the ferroelectric properties, thus opening new insights towards passive component integration.